Pengaruh Motivasi dan Kepuasan Kerja terhadap Kinerja Petugas Kesehatan Masyarakat di Puskesmas Kota Pekalongan - Teguh Irawan; Ardiana Priharwanti; Adika Nggofur Rurrochim; Nia Dewi Amina; Neila Himayati; Nila Afida; Arini Zulfa Laila; Farah Diba Arnis Ardinar; Daffa Rifati Tsania (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
In Pekalongan City there are 14 Community Health Centers under the auspices of the Health Service which are aimed at providing health services to the people in Pekalongan City. Each driver will of course have different performance metrics and results/achievements. Improving employee performance helps puskesmas to survive in the face of unstable competition. Therefore, investment in improving the quality of health services is very important in terms of health service satisfaction. This can be achieved by providing quality services so that patients can trust the Health Center. The purpose of this study was to find out how motivation and job satisfaction affect the performance of public health workers. This research method uses an analytic survey and a cross sectional approach. The results of this study indicate that motivation with a frequency of 0.008 (α=0.05) has an effect on performance and job satisfaction with a frequency of 0.064 (α=0.05) has no effect on performance. This research helps provide knowledge to the community to be more independent and increase the influence of motivation on the performance of public health workers